Freezing COF nanofiltration membrane as well as preparation method and application thereof

The cryogenic COF nanofiltration membrane was prepared by freezing, which solved the problem of heat control in the nanofiltration membrane preparation process. It achieved efficient removal of divalent anions, humic acid and dyes in wastewater, and improved the pure water flux, as well as the stability and lifespan of the membrane.

CN120939768APending Publication Date: 2025-11-14NORTH CHINA ELECTRIC POWER UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511478227.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-16
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

In the current nanofiltration membrane preparation process, it is difficult to control the heat of the interfacial polymerization reaction, resulting in poor membrane density and structural uniformity, which affects separation performance and service life. At the same time, traditional methods may damage the compatibility of membrane materials, making it difficult to achieve efficient retention of divalent anions, humic acid and dyes.

Method used

A frozen COF nanofiltration membrane was prepared by freezing. By lowering the interfacial polymerization temperature, the diffusion rate of amine monomers was controlled, resulting in a nanofiltration membrane with a smooth surface, high pure water flux, and uniform membrane thickness. The freeze-thaw technique was used to form porous channels inside the membrane material, increasing the specific surface area.

Benefits of technology

It achieves efficient retention of divalent anions, humic acid and dyes in wastewater, while improving pure water flux, membrane structure stability and service life. It is simple to operate and suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120939768A_ABST
    Figure CN120939768A_ABST
Patent Text Reader

Abstract

The invention discloses a frozen COF nanofiltration membrane as well as a preparation method and application thereof, and belongs to the technical field of membrane separation. The preparation method comprises the following steps: dissolving 2, 5-diaminobenzene sulfonic acid in deionized water to obtain a water-phase solution, soaking a basement membrane in the water-phase solution, and removing redundant water-phase solution on the surface of the basement membrane; freezing the soaked membrane; dissolving 2, 4, 6-triformyl phloroglucinol in n-caprylic acid to obtain an organic phase solution, soaking the frozen membrane in the organic phase solution to perform interfacial polymerization reaction, and removing the redundant organic phase solution on the surface of the membrane after the reaction is completed to obtain the frozen COF nanofiltration membrane. According to the preparation method disclosed by the invention, 2, 5-diaminobenzene sulfonic acid and 2, 4, 6-triformyl phloroglucinol are used as monomers, and the interfacial polymerization reaction rate is slowed down through freezing, so that efficient interception of divalent anions, humic acid and dyes in the flue gas desulfurization wastewater of the coal-fired power plant is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of membrane separation technology, and particularly relates to a frozen COF (covalent organic framework) nanofiltration membrane, its preparation method and application. Background Technology

[0002] Water resources, as a core element supporting socio-economic development and ensuring basic production activities, play an irreplaceable role in the sustainable operation of human society. However, with the continuous expansion of the global population, the accelerated pace of industrialization, and the increasing prominence of ecological and environmental damage, the imbalance between freshwater supply and demand is intensifying. This has become one of the key bottlenecks restricting the improvement of social productivity and hindering high-quality regional economic development worldwide. The dual challenges of water scarcity and water pollution urgently need to be addressed. Summary of the Invention

[0003] To address the aforementioned technical problems, this invention proposes a frozen COF nanofiltration membrane, its preparation method, and its applications. The prepared membrane exhibits excellent retention effects on divalent anions, humic acid, and dyes in wastewater, while also possessing a high pure water flux.

[0004] Membrane separation technology, as a highly efficient new separation technology, utilizes membrane materials with specific selective permeability to efficiently retain dissolved pollutants (such as ions, small organic molecules, and colloidal particles) in wastewater through physical sieving and chemical adsorption, thereby achieving water purification. Compared to traditional water treatment technologies, membrane separation technology has significant advantages such as high efficiency, low energy consumption, environmental friendliness, small footprint, and ease of operation. It not only effectively reduces the risk of secondary pollution during water treatment but also enables the recycling of water resources. Currently, membrane separation technology has gradually replaced traditional industrial wastewater treatment processes, showing broad application prospects in municipal water supply, industrial wastewater resource utilization, and seawater desalination. It has become one of the most promising technological directions in the field of water resource treatment and reuse, and has been widely promoted and applied in multiple industries such as energy, chemical industry, and environmental protection.

[0005] Nanofiltration (NF), as an important branch of membrane separation technology, offers separation performance between ultrafiltration and reverse osmosis. It can precisely retain organic matter (such as dyes and humic acid) and salt ions (such as divalent anions) with molecular weights ranging from 200 to 2000 Da, making it valuable for applications in advanced industrial wastewater treatment and drinking water purification. The retention efficiency of nanofiltration is synergistically regulated by multiple effects, with the pore size sieving effect (separation based on the difference between membrane pore size and pollutant molecule size) and the Donnan effect (enhancing retention based on the charge interaction between the membrane and pollutants) playing dominant roles. These two factors together ensure the high-efficiency retention of target pollutants such as divalent anions, humic acid, and dyes in wastewater.

[0006] Interfacial polymerization (IP) is one of the core processes for preparing nanofiltration membranes. Essentially, it is a diffusion-controlled exothermic reaction between amine monomers and acyl chloride / aldehyde monomers at the water-organic two-phase interface. The diffusion rate of the amine monomer into the organic phase directly determines the reaction rate of interfacial polymerization and the quality of the formed membrane. Current technologies typically regulate the release rate of the amine monomer by adding an intermediate layer or introducing chemical additives to optimize the membrane structure. However, these methods are all external control measures, which may disrupt the compatibility between the components of the membrane material, leading to decreased membrane performance stability, and they fail to fundamentally solve the problems of reaction rate and heat control during interfacial polymerization.

[0007] Heat, as a core factor influencing monomer diffusion and chemical reactions during interfacial polymerization, remains a subject of limited research. The study by Ben et al. has clearly demonstrated that the large amount of heat released during interfacial polymerization can trigger localized boiling at the two-phase interface or cause dissolved gases to escape from the system, leading to the formation of irregular voids within the prepared membrane. This severely compromises the membrane's compactness and structural uniformity, ultimately affecting its separation performance and lifespan. Therefore, effective thermal control of the interfacial polymerization process is crucial, directly impacting the regulation of the membrane's microstructure and its final performance.

[0008] Meanwhile, the application of freeze-thaw technology in the field of membrane material preparation shows unique advantages: this technology can make the water inside the membrane material form regular ice crystals through low-temperature freezing. The ice crystals will leave a large number of interconnected porous channels during the subsequent sublimation process, which can not only significantly increase the specific surface area of ​​the membrane, but also reduce the resistance of water molecules to permeation, thereby effectively improving the pure water flux of the membrane.

[0009] Therefore, the present invention provides a frozen COF nanofiltration membrane prepared by freezing method, which has a good retention effect on divalent anions, humic acid and dyes in wastewater, and also has a high pure water flux.

[0010] The technical solution provided by this invention is as follows:

[0011] One objective of this invention is to provide a method for preparing a frozen COF nanofiltration membrane, comprising the following steps:

[0012] (1) Dissolve 2,5-diaminobenzenesulfonic acid (DABS) in deionized water to obtain an aqueous solution. Immerse the basement membrane in the aqueous solution to remove excess aqueous solution from the surface of the basement membrane.

[0013] (2) Freeze the soaked membrane;

[0014] (3) Dissolve 2,4,6-tricarboxymethyl phloroglucinol (Tp) in octanoic acid to obtain an organic phase solution. Immerse the frozen membrane in the organic phase solution to carry out interfacial polymerization reaction. After the reaction is completed, remove the excess organic phase solution from the membrane surface to obtain the frozen COF nanofiltration membrane.

[0015] The base membrane is a polyacrylonitrile (PAN) base membrane, a polyethersulfone (PES) base membrane, or a polyvinylidene fluoride (PVDF) base membrane.

[0016] This invention slows down the diffusion rate of amine monomers by reducing the interfacial polymerization reaction temperature, thereby achieving precise control of the membrane growth process. Ultimately, it produces a high-performance frozen COF nanofiltration membrane with a smooth surface, high pure water flux, and uniform membrane thickness, providing a new approach to solving the problems of thermal runaway and performance optimization in the existing nanofiltration membrane preparation process.

[0017] Furthermore, the molar concentration of 2,5-diaminobenzenesulfonic acid in the aqueous solution is 0.42-3.33 mmol / L.

[0018] Furthermore, the basement membrane is immersed in the aqueous solution for 30 minutes.

[0019] Furthermore, the freezing process involves removing the membrane from the aqueous solution, wiping the surface moisture with filter paper, and then freezing it in a -20°C freezer for 0-6 hours, but not 0 hours.

[0020] Furthermore, the molar concentration of 2,4,6-tricarboxymethylphloroglucinol in the organic phase solution is 0.27-2.13 mmol / L.

[0021] Furthermore, the interfacial polymerization reaction takes 0.5-3 days.

[0022] Furthermore, the removal of excess organic phase solution from the membrane surface in step (3) refers to washing with anhydrous ethanol and deionized water in sequence, followed by drying in a vacuum drying oven at 60°C for 12 hours.

[0023] Furthermore, the polyacrylonitrile base film is UN100 with a molecular weight cutoff of 10 kW Da.

[0024] The second objective of this invention is to provide a frozen COF nanofiltration membrane, which is prepared by the above-described preparation method.

[0025] The third objective of this invention is to provide an application of a frozen COF nanofiltration membrane in the treatment of divalent anions, humic acid, and dyes in flue gas desulfurization wastewater from coal-fired power plants.

[0026] Furthermore, the divalent anion is sulfate; the dye is Congo Red, Chrome Black T, or Methyl Blue.

[0027] Compared with the prior art, the present invention has the following advantages and technical effects:

[0028] (1) The present invention uses a freezing method to prepare a membrane, thereby slowing down the diffusion rate by reducing the reaction temperature, thus forming a nanofiltration membrane with a smooth surface, high flux and small thickness;

[0029] (2) The hybrid nanofiltration membrane preparation method of the present invention is simple to operate, has a short process flow, mild operating conditions, and high membrane preparation efficiency, and is suitable for widespread application.

[0030] (3) The present invention uses freeze-thaw technology to form ice crystals inside the membrane material and leaves porous channels after sublimation, thereby increasing the specific surface area of ​​the membrane and improving the pure water flux. The membrane after being soaked in the aqueous solution is subjected to freeze treatment. By changing the physical state of the monomer through freezing, the diffusion rate of the aqueous monomer and the reaction thermodynamics can be controlled, thereby reducing the interfacial polymerization reaction rate with the organic monomer.

[0031] (4) The frozen COF nanofiltration membrane prepared in this invention can increase the pure water flux from 1.12 to 223.62 L / (h·m) by freezing. 2 • MPa), used to treat divalent anions, humic acid, and dyes in flue gas desulfurization wastewater from coal-fired power plants. Attached Figure Description

[0032] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:

[0033] Figure 1 This is a flowchart illustrating the preparation process of the frozen COF nanofiltration membrane in Examples 1-16 of the present invention;

[0034] Figure 2 The graphs show the performance of the frozen COF nanofiltration membranes prepared at different polymerization reaction times in Examples 1-6.

[0035] Figure 3 The graph shows the effect of different freezing times on the performance of frozen COF nanofiltration membranes in Examples 7-12.

[0036] Figure 4 The graph shows the effect of different concentration ratios on the performance of the frozen COF nanofiltration membrane in Examples 12-16. Detailed Implementation

[0037] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0038] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0039] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0040] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0041] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0042] This invention provides a method for preparing a frozen COF nanofiltration membrane, comprising the following steps:

[0043] (1) Dissolve 2,5-diaminobenzenesulfonic acid (DABS) in deionized water to obtain an aqueous solution. Immerse the basement membrane in the aqueous solution to remove excess aqueous solution from the surface of the basement membrane.

[0044] (2) Freeze the soaked membrane;

[0045] (3) Dissolve 2,4,6-tricarboxymethyl phloroglucinol (Tp) in octanoic acid to obtain an organic phase solution. Place the frozen membrane in the organic phase solution for interfacial polymerization reaction. After the reaction is completed, remove the excess organic phase solution from the membrane surface to obtain the frozen COF nanofiltration membrane.

[0046] The base membrane is a polyacrylonitrile (PAN) base membrane, a polyethersulfone (PES) base membrane, or a polyvinylidene fluoride (PVDF) base membrane. Exemplarily, in the following preferred embodiments of the present invention, the base membrane is a polyacrylonitrile (PAN) base membrane.

[0047] In the following optional embodiments of the present invention, the molar concentration of 2,5-diaminobenzenesulfonic acid in the aqueous solution is 0.42-3.34 mmol / L. Exemplarily, in the following preferred embodiments of the present invention, the molar concentration of 2,5-diaminobenzenesulfonic acid in the aqueous solution is 0.42 mmol / L, 0.83 mmol / L, 1.67 mmol / L, 2.5 mmol / L, or 3.33 mmol / L.

[0048] In the following optional embodiments of the present invention, the immersion time of the basement membrane in the aqueous solution is 30 min.

[0049] In the following optional embodiments of the present invention, the freezing process involves removing the membrane from the aqueous solution, wiping the surface moisture with filter paper, and then freezing it in a -20°C freezer for 0-6 hours. Exemplarily, in the following preferred embodiments of the present invention, the freezing time is 0 hours, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, or 6 hours.

[0050] In the following optional embodiments of the present invention, the molar concentration of 2,4,6-tricarboxymethyl phloroglucinol in the organic phase solution is 0.27-2.13 mmol / L. Exemplarily, in the following preferred embodiments of the present invention, the molar concentration of 2,4,6-tricarboxymethyl phloroglucinol in the organic phase solution is 0.27 mmol / L, 0.53 mmol / L, 1.07 mmol / L, 1.6 mmol / L, or 2.13 mmol / L.

[0051] In the following optional embodiments of the present invention, the interfacial polymerization reaction time is 0.5-3 days. Exemplarily, in the following preferred embodiments of the present invention, the interfacial polymerization reaction time is 0.5 days, 1 day, 1.5 days, 2 days, 2.5 days, or 3 days.

[0052] In the following optional embodiments of the present invention, the removal of excess organic phase solution from the membrane surface in step (3) refers to washing with anhydrous ethanol and deionized water in sequence, followed by drying in a vacuum drying oven at 60°C for 12 hours.

[0053] In the following optional embodiments of the present invention, the polyacrylonitrile base film is UN100 with a molecular weight cutoff of 10 kW Da.

[0054] A frozen COF nanofiltration membrane can be prepared using the above preparation method.

[0055] The frozen COF nanofiltration membrane can be used to treat divalent anions, humic acid, and dyes in flue gas desulfurization wastewater from coal-fired power plants.

[0056] The divalent anion is sulfate; the dye is Congo Red, Chrome Black T, or Methyl Blue.

[0057] For example, this embodiment of the invention provides a method for preparing a frozen COF nanofiltration membrane, comprising the following steps: immersing a PAN substrate membrane in an aqueous solution of 2,5-diaminobenzenesulfonic acid (DABS) for 30 min; removing the membrane and freezing it at -20°C for 6 h; immersing the frozen membrane in an organic solution of 2,4,6-tricarboxymethyl phloroglucinol (Tp) for interfacial polymerization reaction for 0.5-3 days; and finally washing and drying to obtain the frozen COF nanofiltration membrane.

[0058] The PAN is UN100 with a molecular weight cutoff of 10 kDa.

[0059] The 2,5-diaminobenzenesulfonic acid (DABS) aqueous solution refers to 40 mL of an aqueous solution of 2.5 mmol / L DABS.

[0060] The freezing process involves removing the membrane from the aqueous solution, wiping the surface moisture with filter paper, and then freezing it in a -20°C freezer for 6 hours.

[0061] The 2,4,6-tricarboxymethyl phloroglucinol (Tp) organic phase solution refers to 30 mL of 1.6 mmol / L Tp octanoic acid solution.

[0062] The cleaning and drying process refers to cleaning with anhydrous ethanol and deionized water in sequence, followed by drying in a vacuum drying oven at 60°C for 12 hours.

[0063] All raw materials used in this invention were purchased commercially. The polyacrylonitrile membrane UN100 was purchased from Beijing Zhongke Ruiyang Membrane Technology Co., Ltd. In addition, the vacuum drying, ultrasonication and other steps in the preparation process of this invention are conventional technical means in the field and are not intended to limit the technical solution of this invention.

[0064] The technical solution of the present invention will be further illustrated by the following embodiments.

[0065] Figure 1 This is a flowchart illustrating the preparation process of the frozen COF nanofiltration membrane in Examples 1-16 of the present invention.

[0066] Example 1

[0067] A method for preparing a frozen COF nanofiltration membrane includes the following steps:

[0068] Step 1: Preparation of reaction solution: Weigh 18.82 mg of 2,5-diaminobenzenesulfonic acid (DABS) into 40 mL of deionized water, sonicate for 5 min to obtain 40 mL of aqueous solution with a concentration of 2.5 mmol / L; take 10.09 mg of 2,4,6-tricarboxymethyl phloroglucinol (Tp) into 30 mL of n-octanoic acid solution, sonicate for 5 min to obtain 30 mL of organic solution with a concentration of 1.6 mmol / L.

[0069] Step 2: Preparation of COF / PAN membrane: The PAN substrate membrane with a diameter of 7cm was cut and immersed in the aqueous solution for 30min. After being taken out and dried with filter paper, it was frozen at -20℃ for 6h. Then it was immersed in the organic solution for 0.5d to carry out the interfacial polymerization reaction.

[0070] Step 3: Cleaning the COF / PAN membrane: After the reaction, the membrane is taken out and washed with anhydrous ethanol and deionized water in sequence, and then dried in a vacuum drying oven at 60°C for 12 hours to obtain a frozen COF nanofiltration membrane.

[0071] Example 2

[0072] A method for preparing a frozen COF nanofiltration membrane includes the following steps:

[0073] Step 1: Preparation of reaction solution: Weigh 18.82 mg of 2,5-diaminobenzenesulfonic acid (DABS) into 40 mL of deionized water, sonicate for 5 min to obtain 40 mL of aqueous solution with a concentration of 2.5 mmol / L; take 10.09 mg of 2,4,6-tricarboxymethyl phloroglucinol (Tp) into 30 mL of n-octanoic acid solution, sonicate for 5 min to obtain 30 mL of organic solution with a concentration of 1.6 mmol / L.

[0074] Step 2: Preparation of COF / PAN membrane: The PAN substrate membrane with a diameter of 7cm was cut and soaked in the aqueous solution for 30min. After being taken out and dried with filter paper, it was frozen at -20℃ for 6h. Then it was soaked in the organic solution for 1d to carry out the interfacial polymerization reaction.

[0075] Step 3: Cleaning the COF / PAN membrane: After the reaction, the membrane is taken out and washed with anhydrous ethanol and deionized water in sequence, and then dried in a vacuum drying oven at 60°C for 12 hours to obtain a frozen COF nanofiltration membrane.

[0076] Example 3

[0077] Same as Example 1, except that the interfacial polymerization reaction time in step two is 1.5 days, resulting in a frozen COF nanofiltration membrane.

[0078] Example 4

[0079] Same as Example 1, except that the interfacial polymerization reaction time in step two is 2 days, resulting in a frozen COF nanofiltration membrane.

[0080] Example 5

[0081] Same as Example 1, except that the interfacial polymerization reaction time in step two is 2.5 days, resulting in a frozen COF nanofiltration membrane.

[0082] Example 6

[0083] Same as Example 1, except that the interfacial polymerization reaction time in step two is 3 days, resulting in a frozen COF nanofiltration membrane.

[0084] Example 7

[0085] Same as Example 2, except that no freezing process is performed in step two, i.e., the freezing time is 0h.

[0086] Example 8

[0087] Same as Example 2, except that the freezing time in step two is 1 hour.

[0088] Example 9

[0089] Same as Example 2, except that the freezing time in step two is 2 hours.

[0090] Example 10

[0091] Same as Example 2, except that the freezing time in step two is 3 hours.

[0092] Example 11

[0093] Same as Example 2, except that the freezing time in step two is 4 hours.

[0094] Example 12

[0095] A method for preparing a frozen COF nanofiltration membrane includes the following steps:

[0096] Step 1: Preparation of reaction solution: Weigh 18.82 mg of 2,5-diaminobenzenesulfonic acid (DABS) into 40 mL of deionized water, sonicate for 5 min to obtain 40 mL of aqueous solution with a concentration of 2.5 mmol / L; take 10.09 mg of 2,4,6-tricarboxymethyl phloroglucinol (Tp) into 30 mL of n-octanoic acid solution, sonicate for 5 min to obtain 30 mL of organic solution with a concentration of 1.6 mmol / L.

[0097] Step 2: Preparation of COF / PAN membrane: The PAN substrate membrane with a diameter of 7cm was cut and soaked in the aqueous solution for 30min. After being taken out and dried with filter paper, it was frozen at -20℃ for 5h. Then it was soaked in the organic solution for 1d to carry out the interfacial polymerization reaction.

[0098] Step 3: Cleaning the COF / PAN membrane: After the reaction, the membrane is taken out and washed with anhydrous ethanol and deionized water in sequence, and then dried in a vacuum drying oven at 60°C for 12 hours to obtain a frozen COF nanofiltration membrane.

[0099] Example 13

[0100] Same as Example 12, except that step one is as follows: Weigh 3.14 mg of 2,5-diaminobenzenesulfonic acid (DABS) into 40 mL of deionized water, sonicate for 5 min to obtain 40 mL of aqueous solution with a concentration of 0.42 mmol / L; take 1.18 mg of 2,4,6-tricarboxymethyl phloroglucinol (Tp) into 30 mL of octanoic acid solution, sonicate for 5 min to obtain 30 mL of organic solution with a concentration of 0.27 mmol / L.

[0101] Example 14

[0102] Same as Example 12, except that step one is as follows: 6.27 mg of 2,5-diaminobenzenesulfonic acid (DABS) is weighed into 40 mL of deionized water and sonicated for 5 min to obtain 40 mL of aqueous solution with a concentration of 0.83 mmol / L; 3.36 mg of 2,4,6-tricarboxymethyl phloroglucinol (Tp) is weighed into 30 mL of octanoic acid solution and sonicated for 5 min to obtain 30 mL of organic solution with a concentration of 0.53 mmol / L.

[0103] Example 15

[0104] Same as Example 12, except that step one is as follows: Weigh 12.55 mg of 2,5-diaminobenzenesulfonic acid (DABS) into 40 mL of deionized water, sonicate for 5 min to obtain 40 mL of aqueous solution with a concentration of 1.67 mmol / L; take 6.72 mg of 2,4,6-tricarboxymethyl phloroglucinol (Tp) into 30 mL of octanoic acid solution, sonicate for 5 min to obtain 30 mL of organic solution with a concentration of 1.07 mmol / L.

[0105] Example 16

[0106] Same as Example 12, except that step one is as follows: Weigh 25.09 mg of 2,5-diaminobenzenesulfonic acid (DABS) into 40 mL of deionized water, sonicate for 5 min to obtain 40 mL of aqueous solution with a concentration of 3.33 mmol / L; take 13.45 mg of 2,4,6-tricarboxymethyl phloroglucinol (Tp) into 30 mL of octanoic acid solution, sonicate for 5 min to obtain 30 mL of organic solution with a concentration of 2.13 mmol / L.

[0107] Performance testing:

[0108] The separation performance of the frozen COF nanofiltration membranes prepared in Examples 1-16 was evaluated, mainly by four characteristic parameters: pure water flux, salt rejection rate, humic acid rejection rate, and dye rejection rate.

[0109] Pure water flux (LMH / MPa) is defined as the volume of water passing through the effective membrane area per unit pressure and unit time under certain operating pressure conditions. Unless otherwise specified, the test pressure of the membrane is 0.2 MPa.

[0110] Salt rejection rate calculation formula: R = (1 - σ1 / σ2) × 100%, where R represents the rejection rate, σ1 and σ2 are the conductivity (us / cm) of the permeate and feed liquid, respectively. Unless otherwise specified, the feed liquid is 1 g / L of (NH4)2SO4.

[0111] Formula for calculating dye or humic acid retention rate: R = (1 - C) p / C f ) × 100%, where R represents the retention rate, C f and C p These are the dye concentrations (g / L) in the feed solution and the filtrate, respectively. Unless otherwise specified, the feed solution is a 0.1 g / L dye or humic acid solution.

[0112] The results are shown in Tables 1-3.

[0113] Table 1. Separation performance test results of the frozen COF nanofiltration membranes prepared in Examples 1-6

[0114] <![CDATA[Water flux, L / (h·m 2 ·Mpa)]]> <![CDATA[(NH4)2SO4,%]]> Methyl blue, % Chrome Black T, % Congo Red, % Humic acid, % Example 1 223.62 20.56 82.73 99.99 99.99 99.99 Example 2 91.99 29.75 91.28 99.99 99.99 99.99 Example 3 42.99 29.13 92.35 99.99 99.99 99.99 Example 4 14.65 29.02 92.55 99.99 99.99 99.99 Example 5 10.45 27.02 97.78 99.99 99.99 99.99 Example 6 7.32 30.46 93.06 99.99 99.99 99.99

[0115] Table 1 shows that, compared to Examples 1-6, the extended interfacial polymerization reaction time resulted in a more complete cross-linking reaction between the aqueous and organic monomers, forming a thicker COF layer. As the reaction proceeds, the pore size of the COF layer gradually decreases, leading to a denser structure and ultimately a reduction in pure water flux. The extended reaction time resulted in a tighter cross-linking of the COF network, a more uniform pore size distribution, and an increased proportion of small pores, leading to a higher rejection rate for ammonium sulfate and methylene blue. Compared to Example 1, the rejection rates of (NH4)2SO4 and methylene blue in Examples 2-6 showed little change, while the rejection rates of Congo red, Eriochrome Black T, and humic acid in Examples 1-6 all reached 99.99%.

[0116] Table 2. Test results of separation performance of the frozen COF nanofiltration membranes prepared in Examples 2 and 7-12.

[0117] <![CDATA[Water flux, L / (h·m 2 ·Mpa)]]> <![CDATA[(NH4)2SO4 rejection rate, %]]> Methyl blue, % Chrome Black T, % Congo Red, % Humic acid, % Example 2 91.99 29.75 91.28 99.99 99.99 99.99 Example 7 1.12 61.45 95.32 99.99 99.99 99.99 Example 8 3.73 60.22 94.28 99.99 99.99 99.99 Example 9 8.95 59.00 95.00 99.99 99.99 99.99 Example 10 11.29 59.30 95.62 99.99 99.99 99.99 Example 11 13.80 55.75 96.14 99.99 99.99 99.99 Example 12 73.49 37.93 93.23 99.99 99.99 99.99

[0118] Table 2 shows that, compared to Examples 2 and 7-12, during the freezing process, water in the aqueous solution forms ice crystals. Their growth compresses the polymer chains and aqueous monomers in the PAN substrate membrane, forming oriented pores or channels. Prolonged freezing time leads to larger ice crystal size, resulting in larger pores and a more porous structure within the membrane. This structure increases water transport paths and improves pure water flux, but also reduces sieving capacity, leading to a decrease in rejection rate. Compared to Examples 2 and 7-12, the rejection rate of methylene blue did not change significantly, while the rejection rates of Congo red, chrome black T, and humic acid in Examples 2 and 7-12 all reached 99.99%.

[0119] Table 3. Separation performance test results of the frozen COF nanofiltration membranes prepared in Examples 12-16

[0120] <![CDATA[Water flux, L / (h·m 2 ·Mpa)]]> <![CDATA[(NH4)2SO4 rejection rate, %]]> Methyl blue, % Chrome Black T, % Congo Red, % Humic acid, % Example 12 73.49 37.93 93.23 99.99 99.99 99.99 Example 13 113.06 27.06 85.32 99.99 99.99 99.99 Example 14 95.99 33.73 90.62 99.99 99.99 99.99 Example 15 89.05 35.79 91.48 99.99 99.99 99.99 Example 16 62.24 47.95 91.21 99.99 99.99 99.99

[0121] Table 3 shows that, compared to Examples 12-16, the increased monomer concentration led to a more complete polymerization reaction, resulting in a denser membrane structure. This denser structure reduces the porosity of the membrane, increasing the resistance to water molecules passing through, thus reducing the pure water flux. Simultaneously, the denser structure also improves the retention capacity for solute molecules, thereby increasing the ion retention efficiency. Compared to Example 12, the retention rate of methylene blue in Examples 12-16 remained largely unchanged, while the retention rates of Congo red, Eriochrome Black T, and humic acid all reached 99.99%.

[0122] Figure 2The figures show the performance of the frozen COF nanofiltration membranes prepared under different polymerization reaction times in Examples 1-6. As can be seen from the figures, the pure water flux of the COF membrane decreases significantly with the extension of the interfacial polymerization reaction time. Specifically, when the reaction time increases from 0.5 days to 3 days, the pure water flux decreases from 223.62 L / (h・m²・MPa) to 7.32 L / (h・m²・MPa). The core reason is that extending the reaction time allows for more complete cross-linking between the aqueous and organic monomers, forming a thicker COF layer with smaller pore sizes and a denser structure, thus increasing the resistance to water molecule permeation.

[0123] The rejection rates for ammonium sulfate and methylene blue generally increased with increasing reaction time (ammonium sulfate rejection rate increased from 20.56% to 30.46%, and methylene blue rejection rate increased from 82.73% to 93.06%), due to the improved sieving effect caused by the dense COF layer and more uniform pore size distribution (increased proportion of small pores). The rejection rates for Congo red, Eriochrome Black T (representative dye), and humic acid remained stable at 99.99% at all six reaction times, indicating that the molecular size of these pollutants differs significantly from the pore size of the COF membrane and is unaffected by small changes in reaction time, resulting in stable rejection performance.

[0124] Figure 3 The graph shows the effect of different freezing times on the performance of the frozen COF nanofiltration membrane in Examples 7-12. As can be seen from the graph, the pure water flux of the COF membrane increases significantly with the extension of freezing time. Specifically, the freezing time increases from 1.12 L / (h・m²・MPa) at 0 h (room temperature, no freezing) to 91.99 L / (h・m²・MPa) at 6 h. The core mechanism is that during the freezing process, water in the aqueous solution forms ice crystals. The growth of ice crystals compresses the polymer chains and aqueous monomers in the substrate membrane, forming directional pores or channels. Moreover, the longer the freezing time, the larger the ice crystal size, the more unobstructed the pores in the membrane, the looser the structure, and the lower the resistance to water molecule permeation.

[0125] The retention rate of ammonium sulfate decreased with increasing freezing time (from 61.45% at 0h to 29.75% at 6h), because the loose membrane structure reduced the sieving capacity and weakened the retention effect on small-sized ions.

[0126] The rejection rate of methylene blue fluctuated little under different freezing times (85.32%-96.14%), while the rejection rates of Congo red, chrome black T, and humic acid remained at 99.99%. This indicates that freezing time mainly affects the membrane's rejection of small-sized ions, and has no significant interference with the rejection effect of dyes and humic acid with larger molecular sizes.

[0127] Figure 4The graph shows the effect of different concentration factors on the performance of the frozen COF nanofiltration membrane in Examples 12-16. As can be seen from the graph, the pure water flux of the COF membrane decreases with increasing concentrations of aqueous monomer (DABS) and organic monomer (Tp). Specifically, when the concentration increases from 0.25 times to 2 times, the pure water flux decreases from 113.06 L / (h・m²・MPa) to 62.24 L / (h・m²・MPa). This is because the higher monomer concentration leads to a more complete interfacial polymerization reaction, forming a denser COF membrane structure, reducing porosity, and increasing the resistance to water molecule permeation.

[0128] The retention rate of ammonium sulfate increased with increasing monomer concentration (from 27.06% at 0.25 times to 47.95% at 2 times), because the dense membrane structure improved the screening ability for small-sized ions.

[0129] The rejection rate of methylene blue fluctuated little at different concentrations (85.32-93.23%), while the rejection rates of Congo red, chrome black T, and humic acid remained at 99.99%. This indicates that changes in monomer concentration mainly affect the membrane's rejection of small-sized ions, while the rejection effect on macromolecular pollutants is stable.

[0130] In summary, the materials used in this invention are readily available, the preparation process is simple, the process is short, and the operation is convenient. By freezing the base membrane at -20°C, the diffusion rate is slowed down by lowering the reaction temperature, thereby forming a nanofiltration membrane with a smooth surface, high flux, and small thickness.

[0131] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A method for preparing a frozen COF nanofiltration membrane, characterized in that, Includes the following steps: (1) Dissolve 2,5-diaminobenzenesulfonic acid in deionized water to obtain an aqueous solution. Immerse the basement membrane in the aqueous solution to remove excess aqueous solution from the surface of the basement membrane. (2) Freeze the soaked membrane; (3) Dissolve 2,4,6-tricarboxymethyl phloroglucinol in octanoic acid to obtain an organic phase solution. Immerse the frozen membrane in the organic phase solution to carry out interfacial polymerization reaction. After the reaction is completed, remove the excess organic phase solution from the membrane surface to obtain the frozen COF nanofiltration membrane. The base film is a polyacrylonitrile base film, a polyethersulfone base film, or a polyvinylidene fluoride base film.

2. The preparation method according to claim 1, characterized in that, The molar concentration of 2,5-diaminobenzenesulfonic acid in the aqueous solution is 0.42-2.5 mmol / L.

3. The preparation method according to claim 1, characterized in that, The basement membrane was immersed in the aqueous solution for 30 minutes.

4. The preparation method according to claim 1, characterized in that, The freezing process involves placing the membrane at -20°C for 5-6 hours.

5. The preparation method according to claim 1, characterized in that, The molar concentration of 2,4,6-tricarboxymethylphloroglucinol in the organic phase solution is 0.27-1.6 mmol / L.

6. The preparation method according to claim 1, characterized in that, The time for the interfacial polymerization reaction is 0.5-1 day.

7. The preparation method according to claim 1, characterized in that, The polyacrylonitrile base film is UN100 with a molecular weight cutoff of 10 kW Da.

8. A cryogenic COF nanofiltration membrane, characterized in that, It is prepared by the preparation method described in any one of claims 1-7.

9. The application of the frozen COF nanofiltration membrane as described in claim 8 in the treatment of divalent anions, humic acid and dyes in flue gas desulfurization wastewater from coal-fired power plants.

10. The application according to claim 9, characterized in that, The divalent anion is sulfate; the dye is Congo Red, Chrome Black T, or Methyl Blue.